2019
DOI: 10.1103/physrevb.99.235419
|View full text |Cite
|
Sign up to set email alerts
|

Full electrostatic control of quantum interference in an extended trenched Josephson junction

Abstract: Hybrid semiconductor/superconductor devices constitute an important platform for a wide range of applications, from quantum computing to topological-state-based architectures. Here, we demonstrate full modulation of the interference pattern in a superconducting interference device with two parallel islands of ballistic InAs quantum wells separated by a trench, by acting independently on two side-gates. This so far unexplored geometry enables us to tune the device with high precision from a SQUID-like to a Frau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Second, we report on the realization of hybrid Josephson junctions formed by an InAs quantum well between two Nb contacts. 29,30 Here, we demonstrate supercurrent flow, whose amplitude can be tuned acting on two side gates, with Nb critical fields of the order of 3T. It has been shown that in these structures, at these magnetic fields, well-developed quantum Hall plateaus appear, 29 allowing for the study of the coexistence of superconducting correlations and quantum Hall regime, [31][32][33] two important ingredients for the emergence of topological quasiparticles in 2DEG-based hybrid structures.…”
Section: Introductionmentioning
confidence: 78%
“…Second, we report on the realization of hybrid Josephson junctions formed by an InAs quantum well between two Nb contacts. 29,30 Here, we demonstrate supercurrent flow, whose amplitude can be tuned acting on two side gates, with Nb critical fields of the order of 3T. It has been shown that in these structures, at these magnetic fields, well-developed quantum Hall plateaus appear, 29 allowing for the study of the coexistence of superconducting correlations and quantum Hall regime, [31][32][33] two important ingredients for the emergence of topological quasiparticles in 2DEG-based hybrid structures.…”
Section: Introductionmentioning
confidence: 78%
“…Recently, the possibility to employ quantum point contacts [23] instead of magnetic barriers has been considered, providing a promising alternative for topological insulator-based Majorana platforms [24,25]. Several other platforms have been proposed, ranging from ferromagnetic atomic chains with superconducting pairing [26], planar Josephson junctions in 2D semiconductors [27][28][29], and the more popular setup based on spin-orbit-coupled quantum wire with proximity superconductivity and applied magnetic fields [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, it has become possible to investigate such transport problems not only between identical ballistic chiral QH states but also between distinct systems, such as QH edge states and superconductors, both theoretically [61][62][63][64][65][66][67][68][69][70] and experimentally [19,20,22,[71][72][73][74]. This line of research is particularly relevant for the creation of parafermion bound states, non-Abelian quasiparticles with potential application in topological quantum computation [75][76][77][78][79][80][81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%